Development of low-phosphorus tolerant rice culture WGL-1495 through protein kinase OsPSTOL (Pup1) introgression using restricted marker-assisted breeding - Hari, Y; Uma, R R; Ashwini, D; Rajendra, K P; Neelima, G; Sundaram, R M; Anantha, M S; Anila, M; Edukondalu, B; Ramulu, Ch; et al. (Plant Science Today, 2025)
The study aimed to improve phosphorus use efficiency in rice through the introgression of the Pup1 QTL from Swarna into MTU1121 using a marker-assisted backcross breeding strategy. Forty F₁ plants were generated and 25 true F₁ plants were identified using markers K20-2BspeI and K46-1. These were backcrossed with MTU1121 to produce 180 BC1F1 plants, of which 86 were Pup1 positive. Eight BC1F1 plants phenotypically resembling MTU1121 were selfed to produce 320 BC1F2 plants, with 25 homozygous plants advancing to BC1F3, BC1F4 and BC1F5 generations. Under normal phosphorus conditions, BC1F5 lines demonstrated a 24.68 % yield increase over MTU1121. Under low phosphorus conditions, WGL-1495 (IET 30233) showed superior performance, with traits such as higher grain yield, panicle length and 1000-grain weight compared to MTU1121. In AICRP trials (2021-2023), WGL-1495 consistently outperformed checks under stress-prone conditions both in 0 % and 50 % recommended dose of phosphorus conditions. It achieved 34 % higher yields than Swarna under zero phosphorus conditions in Zone VII during Kharif 2023. WGL-1495 also exhibited exceptional yields in Karnataka, Telangana and Jharkhand, demonstrating its adaptability and efficiency under phosphorus-stress environments. The potential of WGL-1495 as a promising phosphorus-efficient rice culture for sustainable cultivation in low-phosphorus soils.